Effects of meal type on the bioavailability of vutiglabridin, a novel anti‐obesity agent, in healthy subjects - Heejae Won; Deok Yong Yoon; Sangmi Lee; Joo‐Youn Cho; Jaeseong Oh; In‐Jin Jang; Sang‐Ku Yoo; Kyung‐Sang Yu (Clinical and Translational Science, 2024)
Abstract Vutiglabridin, which affects the pharmacokinetics (PKs) of food, is currently under clinical development for the treatment of obesity. This study aimed to evaluate the effects of low‐ and high‐fat meals on PKs of vutiglabridin in healthy male subjects. A randomized, open‐label, single‐dose, three‐period, six‐sequence crossover study was conducted. The subjects received a single oral dose of vutiglabridin 480 mg in a fasted state, 30 min after the intake of a low‐fat meal (total 500–600 kcal, fat content 100–125 kcal) and high‐fat meal (total 800–1000 kcal, fat content 500–600 kcal), with a 21‐day washout period. Geometric mean ratios (GMRs) and 90% confidence intervals (CIs) for maximum plasma concentration (Cmax) and area under the plasma concentration‐time curve to the last measurable timepoint (AUClast) were calculated. After intake of low‐ and high‐fat meals, systemic exposure to vutiglabridin was increased, and the time to reach Cmax (Tmax) was delayed compared to that in the fasted state. The GMRs (90% CIs) of low‐fat meal to fasted state for Cmax and AUClast were 2.14 (1.76–2.60) and 2.15 (1.92–2.42), respectively, and those of high‐fat meal to fasted state were 3.07 (2.53–3.72) and 3.00 (2.67–3.37), respectively. The median Tmax was delayed by 1.5 h in both fed states compared with that in the fasted state. The study drug was well‐tolerated after administration in both the fed and fasted states. Food ingestion substantially increased the extent of oral vutiglabridin absorption in healthy subjects, and this enhancement increased with the fat content of the meal.